Pevonedistat, a NEDD8-activating enzyme inhibitor, is active in mantle cell lymphoma and enhances rituximab activity in vivo - Czuczman, Natalie M; Barth, Matthew J; Gu, Juan; Neppalli, Vishala; Mavis, Cory; Frys, Sarah E; Hu, Qiang; Liu, Song; Klener, Pavel; Vockova, Petra; Czuczman, Myron S; Hernandez-Ilizaliturri, Francisco J (Blood, 2016)
Mantle cell lymphoma (MCL) is characterized by an aggressive clinical course and inevitable development of refractory disease, stressing the need to develop alternative therapeutic strategies. To this end, we evaluated pevonedistat (MLN4924), a novel potent and selective NEDD8-activating enzyme inhibitor in a panel of MCL cell lines, primary MCL tumor cells, and 2 distinct murine models of human MCL. Pevonedistat exposure resulted in a dose-, time-, and caspase-dependent cell death in the majority of the MCL cell lines and primary tumor cells tested. Of interest, in the MCL cell lines with lower half-maximal inhibitory concentration (0.1-0.5 μM), pevonedistat induced G1-phase cell cycle arrest, downregulation of Bcl-xL levels, decreased nuclear factor (NF)-κB activity, and apoptosis. In addition, pevonedistat exhibited additive/synergistic effects when combined with cytarabine, bendamustine, or rituximab. In vivo, as a single agent, pevonedistat prolonged the survival of 2 MCL-bearing mouse models when compared with controls. Pevonedistat in combination with rituximab led to improved survival compared with rituximab or pevonedistat monotherapy. Our data suggest that pevonedistat has significant activity in MCL preclinical models, possibly related to effects on NF-κB activity, Bcl-xL downregulation, and G1 cell cycle arrest. Our findings support further investigation of pevonedistat with or without rituximab in the treatment of MCL.
Keywords: cyklopentany; regulace genové exprese u nádorů; Animals; apoptóza; Cyclopentanes; pyrimidiny; Caspases; myši SCID; Cell Line, Tumor; Apoptosis; Gene Expression Regulation, Neoplastic; Enzyme Inhibitors; lidé; Cell Cycle Checkpoints; Proto-Oncogene Proteins c-bcl-2; kontrolní body buněčného cyklu; Antineoplastic Agents; protinádorové látky; protoonkogenní proteiny c-bcl-2; Rituximab; lymfom z plášťových buněk; Lymphoma, Mantle-Cell; ubikvitiny; stanovení celkové genové exprese; Mice, SCID; protein NEDD8; Small Molecule Libraries; separace buněk; rituximab; inhibitory enzymů; Cell Separation; Cell Survival; NF-kappa B; kaspasy; zvířata; viabilita buněk; knihovny malých molekul; NEDD8 Protein; Ubiquitins; Gene Expression Profiling; nádorové buněčné linie; Pyrimidines; Humans